PELATIHAN MITIGASI BENCANA KEPADAANAKANAK USIA DINI - Hijrah Purnama Putra (Asian Journal of Innovation and Entrepreneurship, 2014)
Disaster is an event or series of events that threaten and disrupt the lives andlivelihood caused by natural factors or non-natural factors.  Countries Indonesia has thepotential disaster is so large that people have to understand the process of disastermitigation well. The potential of disaster in Indonesia caused the opportunity forcommunity to be a victim is bigger,especially children because of the children are still veryvulnerable and have minimal knowledge related to disaster mitigation. One of area thathas children with minimal knowledge of disaster mitigation is children in the dusunTlogolele. Based on the problem that mentioned before, it made community serviceprograms with the theme of disastermitigation training in the dusun Tlogolele. From theresults of the implementation of the program the children were able to understand theprocess of disaster mitigation and implementation so thatwhenever a disaster undertakenchildren can survive and stay live.